Chinese Postgraduate Choices When Considering a UK Business and Management Programme. (26th October 2015) - Manns, Yihan; Swift, Jonathan
Abstract: This research investigated Chinese students' decision making processes for enrolling on a postgraduate taught business and management programme in a UK university, based on structured interviews, followed by a survey of just over 450 respondents. The validity and reliability of the research instrument were assessed prior to issuing the survey. Convenience sampling was used to collect questionnaires from Chinese students in seven universities in the Northwest of the UK, and the findings were analysed using frequency and factor analysis. The research shows that Chinese students chose a country first, a programme (Business & Management) second, a university third, and a city last; the four choices are determined by 14 factors comprising 42 variables. This study has managerial implications for UK universities' policy makers, managers and practitioners to promote their programmes in China.